Work Stress Mapping of Farmers in Jember Regency - Enggal Hadi Kurniyawan; Nurfika Asmaningrum; Rondhianto; Erti Ikhtiarini Dewi; Alfid Tri Afandi (Postgraduate, University of Mataram, 2025)
Work stress among farmers remains an overlooked occupational health issue in Indonesia despite high vulnerability to economic and environmental pressures. This study aimed to map farmers’ stress levels and identify demographic factors influencing stress. A quantitative descriptive design was used with 140 farmers selected through purposive sampling in Jember Regency. Stress was measured using the DASS-42 stress subscale, and data were analysed descriptively and through multiple linear regression. Results showed that 62.9% of farmers experienced mild stress, 30.7% moderate stress, and 6.4% severe stress. Regression analysis demonstrated that gender (p=0.012), educational attainment (p=0.005), family role (p=0.030), number of family members (p=0.025), land size (p=0.008), and monthly income (p=0.001) significantly influenced stress levels. Female farmers, individuals with low education, heads of households, farmers with more than four family members, land ≤ 0.65 ha, and income < Rp 1,916,983 had markedly higher stress scores. The study concludes that farmer stress is shaped by socioeconomic vulnerability and limited resources. These findings highlight the need for targeted interventions, including capacity-building programs, improved access to agricultural support, and policies that enhance economic stability to reduce work-related stress among Indonesian farmers